KETIDAKADILAN GENDER DALAM NOVEL RONGGENG DUKUH PARUK KARYA AHMAD TOHARI - Puspita Dewi (Humanitatis : Journal of Language and Literature, 2019)
Women become a symbol of who often gets injustice and violence because she was born as female. Literary works are one of the media stories about many things in life including women's lives. Novel Ronggeng Dukuh Paruk by Ahmad Tohari as a research source. The purposes of this study are to identify forms of gender inequality in the Ronggeng Dukuh Paruk novel and analyze the factors that influence on it. The research method used is a qualitative method. The data analysis technique in this study is heuristic and hermeneutic reading. The results showed that forms of gender inequality were found in RDP novels such as sexual violence, female exploitation, and defense of the capitalist system. Sexual violence occurs because there is a system of power and control, Srintil, as a child exploited by the Kertaraja family as adults. The exploitation of women is also lasting because there are elements of kinship or close family relations between those who control and are controlled. Finally, the capitalist system that continues to run in the community, Srintil bought and sold its "virginity" to get gold. The three factors are a crucial part of gender inequality in the novel Ronggeng Dukuh Paruk (RDP) by Ahmad Tohari.